(untitled) (The Research of Medical Science Review, 2024)
Vitamin B12 deficiency is a significant concern among pregnant women, as it can adversely impact both maternal health and fetal development. This cross-sectional study aimed to assess the prevalence and identify risk factors of Vitamin B12 deficiency in pregnant women attending Swat Medical College and Allied Teaching Hospitals in Saidu Shareef, Swat, from January 2022 to June 2024. A sample of 500 pregnant women was selected through probability sampling and evaluated for serum Vitamin B12 levels, with data on demographic, dietary, and socioeconomic variables collected via structured questionnaires. Laboratory assessments determined the presence of deficiency, and statistical analyses, including logistic regression, were conducted to identify associated risk factors. The results indicated a high prevalence of Vitamin B12 deficiency, with approximately 45% of participants below the recommended levels. Key risk factors included low intake of animal-based foods, lower socioeconomic status, and limited health literacy. Our findings underscore the urgent need for public health interventions focused on nutritional counseling, supplementation, and increased awareness of Vitamin B12’s role in pregnancy, particularly in resource-limited regions like Swat. Addressing these factors may improve maternal and fetal health outcomes and reduce the long-term implications of Vitamin B12 deficiency.